Implementation of Graph Colouring Using Welch-Powell Algorithm to Determine Student Mentoring Schedule - Ariestha Widyastuty Bustan; M Rais Salim (Universitas Majalengka, 2019)
Graph colouring using the Welch-Powell algorithm is one of the schedule preparation techniques. Especially for arranging student guidance schedules in a study program. The vertex on a graph is represented as a student who will conduct guidance, while the side that connects two vertex states if the two vertex or two students have one and/or two of the same supervisors. The results of this research indicate that the coloring of graphs using the Welch Powell algorithm can be applied to compile the guidance schedule of PGSD students at the Pacific University of Morotai.